2011
DOI: 10.1128/jvi.00009-11
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and Antiapoptotic Activity of L Protein of Theiler's Murine Encephalomyelitis Virus

Abstract: Viruses frequently have genes with proapoptotic or antiapoptotic activity that may vary in different cell types. The apoptosis that is induced can trigger either a protective or destructive immune response, thereby facilitating virus clearance or persistence of the virus. Apoptotic and antiapoptotic genes have been identified in a number of picornaviruses (reviewed in reference 1). Genes regulating apoptosis in Theiler's murine encephalomyelitis virus (TMEV) have been of special interest because of their poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 27 publications
0
18
1
Order By: Relevance
“…In this regard, it is appropriate to note that L protein of another cardiovirus, Theiler's murine encephalomyelitis virus (TMEV), may exhibit either antiapoptotic or proapoptotic activity in the strain-specific, cell-specific, and context-specific manner (23,46,55). The ability of poliovirus to elicit apoptotic response upon productive infection is markedly cell specific as well (6,28,38,42,51,60).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is appropriate to note that L protein of another cardiovirus, Theiler's murine encephalomyelitis virus (TMEV), may exhibit either antiapoptotic or proapoptotic activity in the strain-specific, cell-specific, and context-specific manner (23,46,55). The ability of poliovirus to elicit apoptotic response upon productive infection is markedly cell specific as well (6,28,38,42,51,60).…”
Section: Discussionmentioning
confidence: 99%
“…In order to delineate the pathogenic region within the DA5ЈUTRLL*P1 subgenomic segment, we prepared DAL/Cre mice, which express only the Recent studies have demonstrated that cardiovirus L protein has a number of activities that are likely to contribute to disease: inhibition of type I IFN gene transcription (11,35,41), inhibition of cellular mRNA export from the nucleus leading to interference with translation (6,23), and regulation of apoptosis (9,27,36). Recent in vitro studies have shown that transfection of an L expression construct of BeAn into BHK-21 cells leads to cell death and apoptosis (9) and that DA L is apoptotic in both BHK-21 and HeLa cells (36). Apoptosis has been identified in varied neural cells in the CNS after TMEV infection of mice, both early after infection and during TMEV-IDD (3, 4, 33, 39); however, the TMEV gene responsible for the apoptosis in infected neural cells has not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…L protein of cardioviruses has been shown to inhibit type I interferon (IFN) gene transcription (11,35,41), inhibit nucleocytoplasmic transport and host cell translation (6,23), and regulate cell apoptosis (9,27,36).…”
mentioning
confidence: 99%
“…TMEV L is a multifunctional protein that is important in neurovirulence, viral RNA encapsidation, anti-IFN activity, and viral persistence (29). In contrast to EMCV L protein, L protein of TMEV has a proapoptotic activity (16,42) or an antiapoptotic activity, depending on the TMEV strain and the particular cell types (57). TMEV L is thought to be an important factor in inducing the pathology found after infection of the mouse.…”
Section: Proteinmentioning
confidence: 99%